Identification and characterisation of a novel aberrant pattern of intron 1 inversion with concomitant large insertion and deletion within the F8 gene - You, Guoling; Chi, Kun; Lu, Yeling; Ding, Qiulan; Dai, Jing; Xi, Xiaodong; Wang, Hongli; Wang, Xuefeng (Thrombosis and Haemostasis, 2014)
Intron 1 inversion (Inv1) is a recurrent causative mutation of haemophilia A (HA) and is responsible for 1–5% of severe HA. Inv1 occurs as a result of intra-chromosomal homologous recombination between int1h-1 within intron 1 and int1h-2 located in approximately 125 kb telomeric to the F8 gene. In this report, we presented a previously undescribed aberrant type of Inv1 with complex genomic rearrangement in a pedigree with severe HA. The breakpoints of the rearrangement were identified by the genome walking technique; copy number variations (CNVs) of the F8 gene and X chromosome were detected by AccuCopy technique, Affymetrix CytoScan HD CNV assay and quantitative PCR (qPCR); the F8 transcripts related to the aberrant Inv1 were analysed by reverse transcription PCR (RT-PCR). We have characterised the exact breakpoints of the complex rearrangement, and determined the location and size of the insertion and deletion. The rearrangements can be summarised as an aberrant pattern of Inv1 with a deletion of 2.56 kb and a duplication of 227.3 kb inserted in the rejoining junction within the F8 gene. Our results suggested that this complex genomic rearrangement was generated by two distinct repair mechanisms of fork stalling and template switching/microhomology-mediated break-induced replication (FoSTeS/MMBIR) and nonallelic homologous recombination (NAHR).
Keywords: Copy number variants; genomic rearrangement; haemophilia A; intron 1 inversion